2007
DOI: 10.1177/0145721707309809
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Risks in Diabetes Self-management

Abstract: Reducing risks involves implementing effective risk reduction behaviors to prevent or slow the progression of diabetes complications. Recognizing risk factors for complications and what constitutes optimal preventive care is an important part of managing diabetes. Intervention studies are lacking in some areas of reducing risks. Further studies are needed to test specific interventions to reduce the risks of diabetes complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…Our results showed that self-care behaviors were linked to microvascular damage in any form, with deeper reductions in Hazard Ratios for physical activity and blood sugar testing. Previous studies have also found similar results, both cross-sectionally as longitudinally [ 49 , 50 ]. However, our study was collected based on self-report data at the time of the interview, and cross-sectionally analyzed.…”
Section: Discussionsupporting
confidence: 81%
“…Our results showed that self-care behaviors were linked to microvascular damage in any form, with deeper reductions in Hazard Ratios for physical activity and blood sugar testing. Previous studies have also found similar results, both cross-sectionally as longitudinally [ 49 , 50 ]. However, our study was collected based on self-report data at the time of the interview, and cross-sectionally analyzed.…”
Section: Discussionsupporting
confidence: 81%
“…Placing higher emphasis on educating patients and equipping them with the tools they need to play an active role in self-care practices has been the recent trend of health care delivery for people with diabetes and other chronic illnesses. In collaboration with the health care team, optimal disease related outcomes, improved quality of life, and greater satisfaction with treatment are attainable for individuals who are empowered to take an active role in the management of their health 7 , 9 , 14 , 16 , 22 . Self-efficacy has been described as behavior specific and dynamic, and identifying a person's perception of their capability in a certain setting or with a certain behavior has often been noted as a preeminent indicator of self-care behavior performance [26] .…”
Section: Introductionmentioning
confidence: 99%
“…11 Persons not receiving DSME/S have a 4-fold increase for developing major diabetes-related complications compared to individuals receiving DSME/S. 12 Despite DSME/S benefits, the majority of persons with diabetes who receive DSME/S is quite small. 11,13 Barriers to accessing DSME/S are substantial: 56% of persons with diabetes mellitus nationally and 54.9% of Arizonans report never having attended a DSME/S class.…”
mentioning
confidence: 99%